The Awakening of the Sleepy European Union: The Enigmatic Role of the EU Sanctioning System Against China - Brunelli, Francesca (HAPSc Policy Briefs Series, 2021)
This paper aims at giving useful hints to understand the European hesitation to deliberately take a side in the debated odi et amo relationship between the Western countries (in particular the US) and the People’s Republic of China, including the special administrative region of Hong Kong. It is a matter of fact that the EU has always been excellent with its dialectic showing pure resentment towards the autonomy dismantlement in Hong Kong, but it ended to be a mere “spectator”. However, for the first time in 30 years, the EU seems to have acknowledged its “responsibilities” with the adoption of the Global Human Rights Sanctions Regime (GHRSR), a bell that, in metaphorical terms, seems to have woken up the Union. A Union now more willing to adopt restrictive measures in the promotion of human rights also against its economic partners.